Quality of Work Life of Nurses in Emergency Departments: A Scoping Review - Rukmasari, Ema Arum; Oktaviana, Mariska; Puspitasari, Mita; Ilmanisa, Nadhira (International Journal of Science and Society, 2025)
The results of this scoping review prove that the quality of nurses' working life in the Emergency Department (ED) is influenced by various emotional, psychological, and structural factors that interact with one another. The levels of burnout and compassion fatigue detected are quite high, indicating significant physical and emotional stress in the ED work environment. However, the presence of compassion satisfaction and effective coping strategies serves as a protective factor that reduces the negative impact of workplace stress. Organizational elements such as management support, availability of resources, and supportive working conditions also play a crucial role in enhancing nurses' well-being. These findings emphasize the importance of structured organizational intervention strategies, training in coping strategies, and strengthening a positive work culture to improve nurses' work life in the ED, which ultimately will have a positive impact on the quality of care and patient safety.